Implementation of the RST (Robust Satellite Techniques) approach on MSG-SEVIRI data: applications for volcanic activity monitoring - F. Marchese; C. Filizzola; N. Pergola; FALCONIERI, ALFREDO; PACIELLO, Rossana; TRAMUTOLI, Valerio (2014)
The Robust Satellite Techniques (RST) is a multitemporal approach of satellite data analysis proposed to study different natural/environmental hazards, including high risk volcanic phenomena. In particular, both thermal features and ash emissions may be investigated by RST, by using two specific configurations of such an approach. These algorithms have been tested on different volcanic areas exploiting data provided by polar satellite sensors, such as the Advanced Very High Resolution Radiometer (AVHRR) and the Moderate Resolution Imaging Spectroradiometer (MODIS), showing a high trade-off between reliability and sensitivity of detection. In this work, the RST exportability on data provided by the Spinning Enhanced Visible Infrared Imager (SEVIRI), onboard Meteosat Second Generation (MSG) satellites, is assessed, by studying some recent eruptive events of Etna (Italy) and Grimsvotn (Iceland) volcanoes. Outcomes of this work confirm that the RST-based algorithms may give an important contribution for mitigating volcanic hazards during major eruptions, especially in the framework of integrated and automated early warning systems.